Teaching the College of Policing pre-employment "Certificate in Knowledge of Policing" to undergraduate students: A student and staff evaluation. Issue 2 (11th May 2015) - Pepper, Ian K.; McGrath, Ruth
Abstract : Purpose: – The purpose of this paper is to assist in identifying the value to the student of the College of Policing approved Certificate in Knowledge of Policing (CKP), whilst identifying some of the challenges encountered by both students and staff. Design/methodology/approach: – The research involved students completing self-administered questionnaires both on commencing their study of the CKP and completing the programme. Written student feedback was also collected and a focus group was facilitated with the academic teaching staff. The research approach adopted was aimed at influencing the development of the programme, whilst establishing the value of the CKP to students. Findings: – The research suggests that completing the CKP did not significantly influence the students' career choice, however, it did have a positive impact on the development of their confidence in terms of applying for the role of a police officer. Both staff and students identified the quantity of the knowledge to be taught and learnt, with staff also reporting the additional benefit to them of refreshing their subject knowledge. Research limitations/implications: – The external validity of this research beyond the sample group is limited, due to, for example, different programmes of study at different institutions, etc., however, the findings are informative. The reliability of the research is good, however, it must also be considered the behaviour of respondents may have been influenced by taking part in the research. Further longitudinal research should be conducted following cohorts of students completing the CKP through initial application to employment. Practical implications: – The CKP is currently viewed by many as an educational package to be completed prior to an application for employment as a police officer, whereas consideration should be given to using the CKP as a way to inform and build an individual's confidence that the police officer role is the career for them, or otherwise. Originality/value: – This research has identified how, amongst this group of students, completing the new concept of a pre-employment CKP, approved by the College of Policing, has increased their confidence in applying to become a police officer. As such, this is of value to those teaching the CKP and the College of Policing.